Novel particulate antibiotic-loaded platforms as sustained drug delivery systems for bone infection treatment - Ferreira, Inês da Fonseca Santos, 1985-1 (2015)
Tese de doutoramento, Farmácia (Tecnologia Farmacêutica), Universidade de Lisboa, Faculdade de Farmácia, 2015